Are measures of pain sensitivity associated with pain and disability at 12-month follow up in chronic neck pain? - Moloney, N.; Beales, Darren; Azoory, R.; Hübscher, M.; Waller, Rob; Gibbons, R.; Rebbeck, T. (2018)
OBJECTIVES: Pain sensitivity and psychosocial issues are prognostic of poor outcome in acute neck disorders. However, knowledge of associations between pain sensitivity and ongoing pain and disability in chronic neck pain are lacking. We aimed to investigate associations of pain sensitivity with pain and disability at the 12-month follow-up in people with chronic neck pain. METHODS: The predictor variables were: clinical and quantitative sensory testing (cold, pressure); neural tissue sensitivity; neuropathic symptoms; comorbidities; sleep; psychological distress; pain catastrophizing; pain intensity (for the model explaining disability at 12 months only); and disability (for the model explaining pain at 12 months only). Data were analysed using uni- and multivariate regression models to assess associations with pain and disability at the 12-month follow-up (n = 64 at baseline, n = 51 at follow-up). RESULTS: Univariable associations between all predictor variables and pain and disability were evident (r > 0.3; p < 0.05), except for cold and pressure pain thresholds and cold sensitivity. For disability at the 12-month follow-up, 24.0% of the variance was explained by psychological distress and comorbidities. For pain at 12 months, 39.8% of the variance was explained primarily by baseline disability. CONCLUSIONS: Neither clinical nor quantitative measures of pain sensitivity were meaningfully associated with long-term patient-reported outcomes in people with chronic neck pain, limiting their clinical application in evaluating prognosis.